Estimation of Global Solar Radiation (GSR) From the Sunshine Hour of Guranshe, Surkhet, Nepal - Homchandra Adhikari; Nurapati Pantha (Bibechana, 2022)
The variation in Global Solar Radiation (GSR) was studied by using experimental data via an automatic weather station (CMP3 pyranometer) located at Guranshe (Surkhet), a hilly area with elevation 2194m from the sea level. Also the estimated sunshine hour data of the area were used to calculate the GSR for the purpose of comparison with the measurements. Our study finds a good agreement between the measured (15.65 MJ/m2/day) and estimated/calculated (19.18 MJ/m2/day) values of annual average GSR. The estimated GSR uses Angstrom-Prescott type model for calculating sunshine hours, and the coefficients (a=0.28) and (b=0.57) were obtained using the Sangeetas and Tiwari model. The annual average estimated sunshine hours was found to be 6.86hr which is suitable for GSR based applications. The measured data were used to study the seasonal, monthly and diurnal variations of GSR. The maximum and minimum values of GSR were found during the spring and summer seasons respectively. The minimum GSR in summer is because of heavy rainfall, high relative humidity, and cloud formation in the sky during the time. The coefficient of regression(R) and the coefficient of determination (R2) were obtained as R=0.881 and R2=0.776 respectively. Here the high value of R (88.1%) indicates that of dependent variable (GSR) is nicely predicted by the independent variables. Also the coefficient of determination (R2) tells us the strength of the relationship between two variables.